Exploring our world - Boehm, Richard G.; Hunkins, Francis P.; Armstrong, David G.; Zike, Dinah (McGraw-Hill Glencoe, 2010)
Unit 1. The world -- Unit 2. The United States and Canada -- Unit 3. Latin America -- Unit 4. Europe -- Unit 5. Russia.